Analisis determinan nilai saham dengan peran valuasi saham sebagai variabel intervening - Verren Marquez; Rumintar J.H. Marpaung (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
The capital market plays an important role in raising funds. However, after the COVID-19 pandemic, the IDX80 index showed fluctuations even though many company had strong fundamentals. This situation raises questions about the relevance of internal factors in determining stock value. This study analyzed the influence of firm size, operational performance, and liquidity on stock value, with Earnings per Share as a mediating variable. Earning per Share is considered a key indicator of stock valuation providing a positive signal to investors. Using a quantitative approach with Partial Least Squares – Structural Equation Modelling through SmartPLS 4, the study included outer model testing, multicollinearity, model fit, and both direct and indirect effect analyses. The results showed that firm size, performance, liquidity, and valuation significantly influence stock valuation. However, only firm size had a direct effect on stock value, while stock valuation mediated the influence of firm size, performance, and liquidity on stock value.